ANALISIS PENGARUH STRUKTUR KEPEMILIKAN SAHAM DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING (Studi Pada Perusahaan LQ45 yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2015) - Angga Prasetia, 13.05.52.0091; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2017)
The purpose of this study is to analyze the effect of stock ownership structure and firm size on the disclosure of intellectual capital with profitability as a moderating variable. The sample used LQ45 company listed in BEI period of 2013-2015. The population is taken by purposive sampling method, and that fulfill the sample selection criteria. The sample used is 118 companies. Analysis that used in this study is multiple regression analysis and regression moderation analysis. The results of this study found that firm size variables have a significant effect on intellectual capital disclosure, while the variable ownership structure has no significant effect on the disclosure of intellectual capital. Profitability does not moderate the effect of stock ownership structure and firm size on intellectual capital disclosure.Keywords: Share Ownership Structure, Company Size, Profitability (ROA), and Intellectual Capital Disclosure